Association of vitamin D and severity of COVID-19 in children - Pegah Karimian; Motahareh Sadat Tahami; Shirin Sayyahfar; Motahare Aghajani Delavar (PAGEPress Publications, 2022)
Vitamin has a major role in the functions of the immune system, and the efficacy of this vitamin in reducing inflammation has been identified. Considering the effects of vitamin D, this study research was performed for investigating the relationship between vitamin D and the severity of COVID-19 in children. This cross-sectional study was performed on 101 children infected with the new coronavirus from September 2020 to October 2021. Information on vitamin D levels, demographic factors, and clinical and laboratory findings were documented in information forms and prepared for statistical analyses. The average of children was 2.85 ± 0.85 years. Low oxygen saturation was observed in 35.3% of infected children. The level of involvement was higher in subjects with vitamin D levels higher than 30 and less than 10 ng/ml (p = 0.04). Clinical signs in cases with deficient and sufficient vitamin D levels were more severe in terms of tachypnea and tachycardia (p = 0.01). Children with vitamin D lower than 10 ng/ml showed more frequency (p = 0.02). Cases with moderate vitamin D had fewer gastrointestinal complications (p = 0.03). Also, oxygen levels were lower in children who had low levels of vitamin D (p = 0.02). Vitamin D levels were associated with levels of involvement, tachycardia, tachypnea, clinical signs, gastrointestinal problems, and O2 levels. Moderate vitamin D levels in children are a critical issue that should be considered.